Introduced Populations of an Invasive Tree Have Higher Soluble Sugars but Lower Starch and Cellulose - Li, Wenrao; Wang, Luwei; Tian, Baoliang; Ding, Jianqing; Siemann, Evan (Frontiers in Plant Science, 2020)
Native and introduced plant populations vary in leaf physiology, biochemistry, and biotic interactions. These aboveground traits may help invasive plants in competition. Because roots determine resource absorption, root physiological traits may also affect invasive plant performance. The aim of this study to test this prediction, using the invasive Chinese tallow tree, Triadica sebifera as a model species. Here we examined carbohydrate (soluble sugar, sucrose, fructose, starch, cellulose) concentrations and mass of roots, stems, leaves along with root water potential and AMF colonization of soil-cultured Triadica sebifera seedlings from 10 native (China) and 10 introduced (USA) populations in a common garden. Significantly, introduced populations had greater stem and leaf mass than native populations but their root masses did not differ, so they had lower R:S. Introduced populations had higher soluble sugar concentrations but lower starch and cellulose concentrations in their leaves, stems and roots. Introduced populations had more negative root water potentials and higher AMF colonization. Together, our results indicate that invasive plants shift their carbohydrate allocation, leading to faster growth and a greater aboveground allocation strategy. Higher AMF colonization and more negative water potential in invasive plants likely facilitate more efficient water absorption by roots. Thus, such physiological variation in root characteristics could play a role in plant invasion success.